2020
DOI: 10.1093/cercor/bhaa263
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Following the Violation of Strong and Weak Prior Beliefs

Abstract: Recent work in psychology and neuroscience has revealed differences in impression updating across social distance and group membership. Observers tend to maintain prior impressions of close (vs. distant) and ingroup (vs. outgroup) others in light of new information, and this belief maintenance is at times accompanied by increased activity in Theory of Mind regions. It remains an open question whether differences in the strength of prior beliefs, in a context absent social motivation, contribute to neural diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Also, evidence highlighted an enhanced activity the bilateral TPJ when mental states information is relevant for the moral judgment (Young & Waytz, 2013). Especially, enhanced activations in the TPJ are observed when an immoral behavior is shown (Kim et al, 2021) compared to a moral social comportment. A suggested explanation is the perception of immoral behavior as containing more intents than moral ones (Brambilla et al, 2019), plausibly recruiting a broader neural circuit.…”
Section: Fmri Glm Resultsmentioning
confidence: 92%
“…Also, evidence highlighted an enhanced activity the bilateral TPJ when mental states information is relevant for the moral judgment (Young & Waytz, 2013). Especially, enhanced activations in the TPJ are observed when an immoral behavior is shown (Kim et al, 2021) compared to a moral social comportment. A suggested explanation is the perception of immoral behavior as containing more intents than moral ones (Brambilla et al, 2019), plausibly recruiting a broader neural circuit.…”
Section: Fmri Glm Resultsmentioning
confidence: 92%
“…It is interesting to discover a reduced negative tendency or even positivity bias among interdependent individuals, in the context that negativity bias is widely found in the research on moral impression updating (Kim et al, 2021; Mende‐Siedlecki et al, 2013; Mende‐Siedlecki & Todorov, 2016; Siegel et al, 2018). We argue that the goals of maintaining a social network and close connections with others drives interdependent individuals to keep their good opinions of others.…”
Section: Discussionmentioning
confidence: 98%
“…Study 2 aimed to confirm the results of study 1 with a narrative description paradigm. This is the most commonly used paradigm in impression updating (e.g., Kim et al, 2021; Mende‐Siedlecki et al, 2013) and manipulates impression updating by presenting inconsistent behavioral descriptions. Given that this topic has not been directly studied in previous research, the results of study 1 might be insufficient to support our hypothesis.…”
Section: Studymentioning
confidence: 99%
“…Classical accounts have posited that this region had a role in distinguishing one's own mental states from others, as revealed by the BOLD response changing when another's beliefs are revealed to be erroneous and different from one's own 40 . More recent theoretical work has argued for a social predictive coding framework for theory of mind postulating errors signals in TPJ 66 and previous studies have reported evidence of rTPJ encoding of both unsigned [67][68][69][70] and signed prediction errors 71 in a range of social contexts and behaviours. rTPJ has also been implicated in tracking the expectation of cooperation of others in public good games 72,73 .…”
Section: Discussionmentioning
confidence: 99%